A proven de novo germline mutation in HNPCC. Issue 12 (1st December 1999) - Kraus, C; Kastl, S; Günther, K; Klessinger, S; Hohenberger, W; Ballhausen, W G
Abstract : Hereditary non-polyposis colon cancer (HNPCC) is a heterogeneous group of tumour predisposition syndromes caused by germline mutations in at least four different mismatch repair genes. HNPCC patients are prone to the development of carcinomas of the intestinal tract and other specific sites. Identification of presumptive HNPCC patients is primarily based on a positive family history of colorectal cancer in at least two generations. In the course of mutation screening of the MLH1 and MSH2 genes in patients manifesting a carcinoma of the HNPCC tumour spectrum before the age of 45 years, we identified a germline MSH2 344delA frameshift mutation in a male proband. This index patient, at the age of 25 years, initially developed a large rectal adenoma that was removed by polypectomy. Ten years later he was operated on for an invasive right sided colon carcinoma in the caecum (International Union Against Cancer (UICC) stage III). The mother and father, aged 61 and 66 years, respectively, were healthy and had no family history of colorectal cancer. Subsequent molecular analyses excluded the germinal MSH2 344delA alteration identified in their son and at the same time paternity was confirmed with a set of informative polymorphic markers. Thus, the genetic alteration identified in our patient definitely represented a de novo germline mutation in one of the major HNPCC genes. This case report of a patient with colorectal cancer at a relatively young age with no family history is intended to encourage mutation screening of the MSH2 and MLH1 genes in similar cases to find out whether this group of patients contains an increased proportion of de novo mutations in mismatch repair genes.